Dynamics of Greenhouse Gases (CH4 and CO2) in Meromictic Lake Burgsee, Germany. Issue 8 (19th August 2022) - Fuchs, Andrea; Casper, Peter; Lewandowski, Jörg
Abstract: Extraordinary amounts of greenhouse gases can be stored within the monimolimnion of meromictic lakes, that is, in the water body which is excluded from mixing events. Lake Burgsee (Thuringia, Germany) is a shallow (depth <5 m) lake with a approximately 24 m deep sinkhole, which is fed by underground brine sources and has formed such a monimolimnion. We investigated the carbon dioxide and methane dynamics in this meromictic lake, from production potentials in the sediment via concentrations in the monimolimnion and mixolimnion to emissions to the atmosphere. In the monimolimnion, we found one of the highest methane concentrations (up to >5 mmol L −1 ) ever reported for a natural freshwater lake, while carbon dioxide concentrations in the water and methane production rates in the sediments were rather ordinary and within the range of holomictic eutrophic lakes. At the thermocline, gas concentrations accumulated to approximately 100 μmol L −1 CH4 and 80–230 μmol L −1 CO2 . Estimated fluxes to the atmosphere reached considerable 3.5 mmol CH4 m −2  d −1 and 1.5 mmol CO2 m −2  d −1 above the sinkhole and 0.8 mmol CH4 m −2  d −1 and 0.4 mmol CO2 m −2  d −1 above the near‐by shallow lake center in 2018. Our results demonstrate that lakes in natural brine areas may provide significant storages and releases of greenhouse gases and require further investigation. Plain Language Summary: In meromictic lakes, the deepest water layer, the monimolimnion, is stagnant and not included in seasonal water circulation. Organic matter continuously sinks down into the oxygen‐free monimolimnion, where it is decomposed into the final gaseous products carbon dioxide (CO2 ) and methane (CH4 ). Lake Burgsee is a meromictic shallow (depth <5 m), brine‐fed lake with a approximately 24 m deep sinkhole. At the bottom of the narrow sinkhole, salinities are as high as in brackish water and cause a chemical stratification of the water body—a monimolimnion—in approximately 18 m depth. CH4 concentrations above the sediment reach >5 mmol L −1, which is more than one order of magnitude higher than at the water surface and among the highest CH4 concentrations found in freshwater lakes worldwide. Further, emissions of CH4 and CO2 from the water to the atmosphere were considerable in 2018, and about four times higher above the sinkhole than above the shallow lake center. These results demonstrate, that lakes in natural brine areas may store and release significant amounts of greenhouse gases and require further investigation. Key Points: In the urban meromictic Lake Burgsee, methane production potentials in the sediment are similar to eutrophic holomictic lakes At its deepest site, it contains one of the highest methane concentrations (>5 mmol L −1 CH4 ) ever reported for a natural freshwater lake Lake Burgsee emits up to >3 mmol m −2  d −1 CH4 to the atmosphere above the sinkhole and <1 mmol m −2  d −1 CH4 at a near‐by shallow site